Comparing the pharmacokinetics of GS-441524 after intravenous and oral administration of remdesivir in New Zealand cats with feline infectious peritonitis - Renner KA; Kimble B; Cattin R; Munday JS; Coggins S (SAGE Publications, 2026)
Objectives The aim of the study was to compare the pharmacokinetics of GS-441524 after intravenous (IV) and oral administration of compounded remdesivir (RDV) at 30 mg/kg, respectively, in cats with clinical feline infectious peritonitis (FIP) and to determine the bioavailability of GS-441524 after oral administration of compounded RDV in this population. Methods A total of 13 client-owned cats with a clinical diagnosis of FIP were prospectively recruited. To reflect real-world use, RDV (30 mg/kg) was administered via a 20-min IV infusion or orally (rounded up to capsule size). Plasma GS-441524 concentrations were measured at eight time points over 24 h after administration. Pharmacokinetic parameters were determined by non-compartment analysis followed by bioavailability calculation. Results Pharmacokinetic analysis of GS-441524 after administration of oral RDV achieved a mean (±SD) Cmax of 1083.36 ± 634.19 ng/ml (coefficient of variation [CV] 59%, range 254.18–1834.73) at a mean time of 5.33 ± 3.93 h (range 2–12) with a mean elimination t1/2 of 11.4 ± 8.00 h (range 4.58–27.01). In contrast, IV RDV administration produced a higher mean GS-441524 Cmax of 6262.54 ± 1118.01 ng/ml (CV 18%, range 5193.40–8134.39) at a mean Tmax 0.67 ± 0.26 h (range 0.5–1) with a mean elimination t1/2 of 6.8 ± 5.55 h (range 3.18–17.85). The mean relative bioavailability of GS-441524 after oral RDV was 30.13%. Bioavailability (range 12–52%) and time to maximum plasma concentrations (2–12 h) were highly variable. Conclusions and relevance The oral bioavailability of the compounded RDV used in this study is low, highly variable and appeared lower in cats with effusive disease, although this difference was not statistically significant. Given the small non-randomised sample, results should be interpreted considering the study limitations. Despite the low bioavailability, survival rates in cats treated with oral RDV are comparable to published outcome studies with injectable RDV and oral GS-441524, indicating that oral RDV is a viable treatment option when GS-441524 is not available.
Keywords: Feline infectious peritonitis; feline coronavirus; GS-441524; remdesivir; nucleotide analogue; antiviral; GS-5734